2014
DOI: 10.1007/s11665-014-0913-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stent Radial Force on Stress Pattern After Deployment: A Finite Element Study

Abstract: The present article presents a method for assessing the radial stiffness of nitinol stents. An idealized stent model was created, and its radial stiffness was calculated by means of finite element modeling. The calculations were validated against experimental measurements. The variation of radial stiffness with geometrical dimensions was calculated, and the effect of increasing radial stiffness on endovascular deployment was analyzed. Peak tensile and compressive stresses as well as stent penetration were calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Interestingly, lack of stent coverage of the common carotid artery was an independent restenosis risk factor [17]. Moreover, the Carotid Wallstent has the lowest radial force [16], reducing the chance of further stent expansion, and it was shown that at higher radial force, the stent has better chances of making the artery conform to its original shape [18]. Non-circular stent cross section may provoke flow disturbances, increase in shear stress and in consequence stimulate neointima proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, lack of stent coverage of the common carotid artery was an independent restenosis risk factor [17]. Moreover, the Carotid Wallstent has the lowest radial force [16], reducing the chance of further stent expansion, and it was shown that at higher radial force, the stent has better chances of making the artery conform to its original shape [18]. Non-circular stent cross section may provoke flow disturbances, increase in shear stress and in consequence stimulate neointima proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The antenna is designed to have a suitable shape and the required radiation efficiency for use in the PA and the length of the antenna from tip to tip is currently set to 37 mm. Additionally, finite element modelling (FEM) and experiments were conducted to identify arterial stress patterns and stent radial forces for different stent strut thickness [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…Heart failure is one of the leading causes of morbidity and mortality worldwide [ 1 – 4 ]. The disease is generally progressive, with the advanced forms of the disease carrying a very poor prognosis, and importantly, it is becoming more resistant to conventional therapy [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the software output radial force between ring structure and venous model was used to calculate the stent pressure as radial force divided by the relative cylinder surface area of the ring structure. The stent penetration was also calculated as difference between the diameter of the first stent vessel contact DC and the contact diameter at equilibrium DE [7].…”
Section: Numerical Simulationmentioning
confidence: 99%
“…3) is about 1.16 mm and the resulting operating point of the stent [7] defined as intersecting pressure-diameter response of the ring structure with the venous model is about 8.92 mm.…”
Section: Deployment Into a Venous Vesselmentioning
confidence: 99%